Potential of Locally Available Clay as Raw Material for Traditional-Ceramic Manufacturing Industries (Journal of Chemical Engineering, 2012)
The traditional white-ware manufacturing industries in Bangladesh use clay as the prime raw material which is mostly imported from abroad. The main reasons are the lack of proper clay refining technolo gy in the country and in some part the unsuitable chemical and structural composition of the locally available naturally occurring clays. Moreover, particle size has also been identified as a major challenge in processing of naturally available clay. These two vital aspects affect plasticity and strength of clay during their processing. The composition and particle size of locally available clay were investigated using X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD) to reveal the potential of these clays for industrial purpose upon refining. XRF analysis showed presence of excess SiO2 content in the form of Silicate, Fe2O3 and TiO2; all of which pose a challenge in the refining process. Moreover the amount of Al2O3 in most of the compositions is also not up to the minimum level. Using the data based on statistics on particle sizes of raw materials of various origins, this experiment was aimed to reveal the composition and properties of locally available clay that can be projected for further refining to make suitable as raw material for whiteware industries. DOI: http://dx.doi.org/10.3329/jce.v26i1.10179 JCE 2011; 26(1): 34-37